2015
DOI: 10.1007/s12035-015-9134-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid Levels and Outcomes After Acute Ischemic Stroke

Abstract: Previous studies assessing the association between serum uric acid levels and neurological outcome after acute ischemic stroke reported conflicting results. A systematic review and meta-analysis were conducted to assess the impact of serum uric acid levels on outcome after acute ischemic stroke. Pubmed, Embase, Web of Science, and Google scholar were searched through September 26, 2014 to identify eligible published or unpublished studies on the association between serum uric acid levels and outcome after acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 39 publications
3
74
2
2
Order By: Relevance
“…5,[7][8][9] Therefore the role of uric acid as a risk factor for acute ischemic stroke is controversial. Hence the present study was conducted to determine risk factor potential of serum uric acid levels in patients with acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[7][8][9] Therefore the role of uric acid as a risk factor for acute ischemic stroke is controversial. Hence the present study was conducted to determine risk factor potential of serum uric acid levels in patients with acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…There are only few studies that have concluded higher levels of serum uric acid being neuroprotective in patients with stroke. 5,[7][8][9] An explanation to this comes from the study which concluded that serum uric acid can work as pro-oxidant under certain circumstances, particularly if the levels of other antioxidants like ascorbic acid are low. 31 Various studies have shown that uric acid can result in endothelial dysfunction which can lead to vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…This recent meta analysis of 8131 acute ischemic stroke patients reports that high uric acid serum level on admission should be regarded as good prognostic marker, suggesting its positive impact on BBB damage. Uric acid as an endogen antioxidant is a promising therapeutic neuroprotective agent [161]. Based on promising animal studies human trials were begun.…”
Section: Uric Acidmentioning
confidence: 99%
“…Fast and accurate determination is very essential to the early diagnosis of the diseases. For instance, the serum uric acid (UA) level can be used as an indicator for the detection of diseases related to purine metabolism [1][2][3] and leukemia pneumonia [4][5][6]. Various analytical methods are developed for the determination of UA.…”
Section: Introductionmentioning
confidence: 99%